2022
DOI: 10.1080/10717544.2022.2039809
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals based pulmonary inhalation delivery system: advance and challenge

Abstract: Pulmonary inhalation administration is an ideal approach to locally treat lung disease and to achieve systemic administration for other diseases. However, the complex nature of the structural characteristics of the lungs often results in the difficulty in the development of lung inhalation preparations. Nanocrystals technology provides a potential formulation strategy for the pulmonary delivery of poorly soluble drugs, owing to the decreased particle size of drug, which is a potential approach to overcome the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…In particular, PS is a mixture of lipids (∼90%) and proteins (∼10%) which is synthesized by type II alveolar cells and secreted into the alveolar space to reduce the surface tension in the alveoli air–liquid interspace, thus preventing alveolar collapse . While the inhaled administration of therapeutics allows their efficient localization to the distal lung, the successful delivery of targeted materials often limited by a thin barrier composed of PS and optimal concentration of therapeutics is not effectively maintained at the level of alveolar epithelium. , Hydrophobic PS proteins B and C (PSP-B and PSP-C) incorporated in the vesicles are responsible for maintaining the mechanical integrity of PS layer in the dynamic environment by modulating the fusion and spreading of PS lipids . Therefore, the transport of hydrophilic agents through the PS layer is more challenging for inhaled small molecules and proteins …”
Section: Introductionmentioning
confidence: 99%
“…In particular, PS is a mixture of lipids (∼90%) and proteins (∼10%) which is synthesized by type II alveolar cells and secreted into the alveolar space to reduce the surface tension in the alveoli air–liquid interspace, thus preventing alveolar collapse . While the inhaled administration of therapeutics allows their efficient localization to the distal lung, the successful delivery of targeted materials often limited by a thin barrier composed of PS and optimal concentration of therapeutics is not effectively maintained at the level of alveolar epithelium. , Hydrophobic PS proteins B and C (PSP-B and PSP-C) incorporated in the vesicles are responsible for maintaining the mechanical integrity of PS layer in the dynamic environment by modulating the fusion and spreading of PS lipids . Therefore, the transport of hydrophilic agents through the PS layer is more challenging for inhaled small molecules and proteins …”
Section: Introductionmentioning
confidence: 99%
“…When PS particles enter the human respiratory system, they first encounter airway mucus, which eliminates large PS particles [ 17 ]. Among those not eliminated, pulmonary macrophages may phagocytize 1-3 μm PS particles, and the small PS particles get into the bronchi and alveoli [ 18 ]. It was reported that NPs could travel from the lung to the bloodstream and lymph nodes [ 19 ], but NPs of more than 50 nm could reside within the lung for a longer time [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A top-down approach for manufacturing drug nanocrystals involves crushing larger solid drug particles into nano-sized particles. Particle size reduction is usually achieved by media milling, high-pressure homogenization, or microfluidization [ 19 , 20 ]. Nanomilling, referring to reducing the size of particulate matter to a nanoscale, is performed mainly in an aqueous solution, using milling media (beads, balls, or pearls).…”
Section: Introductionmentioning
confidence: 99%
“…A bottom-up nanofabrication technique is a method in which nanoparticle-forming materials are entirely dissolved in a solvent and then fabricated to nano-scale particles by precipitation, self-assembly, spray drying, or freeze drying [ 20 , 28 ]. Currently, the methods of manufacturing PLGA nanoparticles rely on a bottom-up process, as described earlier.…”
Section: Introductionmentioning
confidence: 99%